Derivation and validation of heat transfer model for Spark-Ignition engine cylinder head. (5th May 2023) - Hassan, M.A.S.M.; Razlan, Z.M.; Bakar, S.A.; Rahman, A.A.; Rojan, M.A.; Wan, W.K.; Ibrahim, Z.; Ishak, A.A.; Ridzuan, M.J.M.
Highlights: Heat characterisation of a single-cylinder engine head was analysed at nine speeds. Engine thermal conditions are determined by subdividing into multiple zones. Unsteady thermal modelling was conducted and validated experimentally. Thermal topologies present a correct heat path system for the engine cylinder head. Thermal characteristics of the engine increase as the engine speed increases. Abstract: The valve train is located in the engine cylinder head, which has various operational heat transfer mechanisms to accommodate the combustion process. Most heat transfer studies in this area have only addressed medium-to high-power vehicles at a single running speed. In this study, a model of an air-cooled underbone motorcycle valve, valve seat, and engine cylinder head was tested to determine the thermal characteristics using actual engine operating conditions at low, medium, and high engine speeds. One-dimensional thermal simulation analyses were conducted to obtain the instantaneous heat-transfer coefficients of an actual engine. The average thermal value was determined as the boundary condition in the three-dimensional thermal analysis. A three-dimensional model was prepared using the ANSYS commercial computational fluid dynamics software package. The results show that as the engine speed increases, so does the thermal load toward the component in the engine cylinder head. The strongest temperature regions were concentrated around the combustion face. The exhaust valve held most of the heat, with the valve neck recording the highest temperature. For the intake valve, the combustion face registered the majority of the heat. The heat flux intensity was gathered in the contact surface area between the valve and its seat, between the valve stem and guide, and between the stem guide and tip section. A thermal survey was used to validate the three modelling results for two separate engine datasets. The cumulative relative errors for intake and exhaust valve seats for low engine speeds were 3.73% and 0.17%, respectively. The intake and exhaust valve seats had cumulative relative errors of 4.12% and 0.70%, respectively, at intermediate speeds. This methodology provides valuable information for analysing the heat characterisation of air-cooled engines. It can also be a useful blueprint for the automotive industry and other researchers involved in thermal measurements.